Beliefs about voices in voice-hearers: the role of schema functioning. Issue 5 (29th September 2020) - Davenport, Brittany; Jackson, Mike; Grange, James A.; Rydon-Grange, Michelle
Abstract: Background: Evidence is emerging that beliefs about voices are influenced by broader schematic beliefs about the self and others. Similarly, studies indicate that the relationship an individual has with their voice may mirror wider patterns of relating observed in social relationships, which may be influenced by schematic beliefs. Aims: This study examined associations between beliefs about voices and self and other schemas. Furthermore, associations between schemas and the perceived relationship between the hearer and their predominant voice were explored. Method: Forty-four voice-hearing participants were recruited across mental health services. Participants completed self-report measures of beliefs about voices, schema functioning, and relating between the hearer and their voice. Dimensions of voice experience, such as frequency and content, were assessed using a clinician-rated scale. Results: Beliefs about voices correlated with negative voice content and schemas. After controlling for negative voice content, schemas were estimated to predict between 1 and 17% of the variance in the six measured beliefs about voices; three of the associations reached statistical significance. Negative-self schema were the strongest predictors of beliefs about voices, whilst positive-self also showed potential relationships. Schemas also correlated with dimensions of relating between the hearer and their voice. Conclusions: In line with previous research, this study provides evidence that schemas, particularly self-schema, may be important in the development of beliefs about voices. This study offers preliminary findings to suggest that schemas are also associated with the perceived relationship between the hearer and their voice.